Biopolitics and Stunting Treatment: Barriers to Community Participation in Sambas Regency, Indonesia - Rahmaniah, Syarifah Ema; Hasni, Ali Almurthadho; Halida, Halida; Syarmiati, Syarmiati; Ghozali, Ahmad; Rabbani Lubis, Ali Akhbar Abaib Mas (SCAD Independent, 2025)
Stunting remains a major public health issue in Indonesia, especially in border areas like Sambas Regency, where intervention efforts have seen limited success. This study investigates the biopolitical dimensions of stunting by highlighting the disconnect between national policies and local realities, particularly in community participation and behavioral change. Using a qualitative case study in Lela Village, data were collected through interviews, observations, and document analysis. Results indicate that low paternal involvement, reliance on traditional medicine, poor health literacy, and smoking habits hinder prevention efforts. State narratives also tend to overburden mothers while neglecting shared responsibility. Biopolitical and gender based approaches to stunting remain underexplored in Indonesia. Stunting is understood here as a complex interaction of power and knowledge that influences public perspectives and government policy. The study calls for a shift from top-down technical fixes to inclusive strategies that promote gender equity, empower communities, and adapt to socio-cultural contexts. It contributes to the discourse on public health governance by advocating participatory, context-sensitive, and transformative solutions for sustainable stunting reduction.